The Climate Smart System with Water Machine Control - Huda Al-Nayyef (Journal La Multiapp, 2023)
Agriculture is important in shaping economies all across the world. For several years, agricultural goods have been stagnating. As a result, methods to boost agricultural productivity efficiency are required. So, the aim of this paper is to implement and design a smart system to make agriculture smarter. The proposed system is composed of Microcontroller ESP32, DH11 and soil moisture sensors, wi-fi shield, fan, water pump, relay. The system enables to sense the environment and give the reaction based the input data. The system can measure and control the temperature and humidity of the environment. If the temperature and humidity rise, the system can reduce it until reach to satisfied level. Also, the system can auto irrigation the soil when the water level is decreases than pre-define threshold. Furthermore, the system sends an alarm message to the owner over wi-fi network by making a telegram bot when the degree of temperature increased and the level of water decreases. Internet of things (IoT) is utilities to developing this system.